THE SEARCH FOR MEANING OF LIFE IN MITCH ALBOM’S TUESDAYS WITH MORRIE - Rahmahwati, Ummu (LANTERN (Journal on English Language, Culture and Literature), 2014)
People often realize that they need to search the meaning of their life. The main character in the novel Mitch Albom’s Tuesdays with Morrie, Morrie, exemplifies the process of this searching the meaning of life. This study is designed for analyzing how Morrie searches the meaning in life and how this process also influences the supporting character, Mitch, who tries to grasp the meaning in his life. The methods used in this study are library research and psychological approach that relate to the extrinsic analysis. This study uses Viktor Frankl’s existentialism that concentrates on the three pathways in discovering the meaning to analyze the extrinsic aspect of this novel. The analysis shows that Morrie and Mitch successfully find their meaning of life by creating something; experiencing something or encountering people; and taking the attitude toward unavoidable suffering. The good deed they make together is by creating their last project which gives advantages not only for both of them but also for people around them. Experiencing something or encountering people gives both of them a deep understanding about the importance of love and human’s relationship rather than the importance of having materialistic things. Suffering helps both of them to accept everything in their life sincerely. Those efforts successfully change their perception of life to be a better perception that brings them into a better future of life.